(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This guideline describes how the principles of an external audit should apply in a computer environment, including that relating to smaller computers. Auditors unaccustomed to auditing in a computer environment are advised to obtain detailed practical guidance on the particular processing situations which they might meet and on the techniques which they might have to employ. Such auditors are also advised to use the detailed guidance available through their Accountancy Body and to attend appropriate training courses.